Use of combined CZM and XFEM techniques for the patch shape performance analysis on the behavior of a 2024-T3 aluminum structure reinforced with a composite patch (Fracture and Structural Integrity, 2022)
The presence of a geometric discontinuity such as a crack or a notch can cause the failure of a structure during its use. Under various mechanical or thermal stresses, a high concentration of stresses can take place at the level of these discontinuities, which in most cases will lead to the total failure of the structure. The service life of these structures can be improved with the use of the repair technique by bonding a composite patch. This technique is of significant interest in several fields, especially with the use of composite materials. This technique is widely used in aeronautics and ensures a long life of damaged structures. Current research aims to optimize the shape size and fiber's nature of this composite patch in order to ensure good load transfer by reducing the stresses in the damaged area. In this work, a finite element method is used to analysis the effect of the shape of the patch on the global response of a 2024-T3 aluminum structure in the presence of a central circular notch. The composite patch is of the carbon/epoxy type bonded through an A-140 Adekit type adhesive on the damaged part of the plate. The analysis consists in determining the force-displacement curves of the repaired structure by using the combination of the two techniques, XFEM for the damage of the aluminum plate 2024-T3 by the automatic creation of the crack and CZM for the analysis of the adhesive debonding. The analysis takes into account the damage in the plate and in the adhesive. However, for the composite patch, and since there will be no damage, we have just analyzed the effect of its shape and essentially the shape of its edges on the load transfer and consequently on the resistance of the structure under loading in tension. Two main patch shapes have been highlighted, namely the square and circular shape. The results show clearly that the shape of the patch’s edges has an impact on the stresses reduction in the plate and subsequently ensures good resistance in terms of force-displacement curve and consequently delays the peeling of the adhesive.
Keywords: aluminum 2024-T3.; resistance; debonding; patch repair; CZM; XFEM